Machinery's handbook : a reference book for the mechanical engineer, designer, manufacturing engineer, draftsman, toolmaker, and machinist. - Oberg, Erik. 4 0 16; 1881- Oberg, Erik,;Green, Robert E.;McCauley, Christopher J.; 5 (New York, New York : Industrial Press Inc., 1996)
A reference guide for mechanical engineers, designers, manufacturing engineers, draftsmen, and toolmakers that describes the techniques, tools, formulas, and procedures used in manufacturing.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Mechanical engineering;Mechanical engineering -- Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2